2020
DOI: 10.3389/fimmu.2020.582098
|View full text |Cite
|
Sign up to set email alerts
|

Helper Innate Lymphoid Cells in Allogenic Hematopoietic Stem Cell Transplantation and Graft Versus Host Disease

Abstract: Helper Innate Lymphoid Cells (hILCs), including ILC1s, ILC2s, and ILC3s, are mainly localized at the mucosal barriers where they play an important role in tissue regeneration and homeostasis through the secretion of specific sets of cytokines. The recent identification of a circulating ILC precursor able to generate all ILC mature subsets in physiological conditions, suggests that "ILC-poiesis" may be important in the context of hematopoietic stem cell transplantation (HSCT). Indeed, in HSCT the conditioning r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Pharmacological targeting of the JAK-STAT pathway was significantly efficacious in both the acute and chronic GvHD preclinical models tested. However, several pathological mechanisms utilize downstream signaling pathways that are potentially JAK-STAT-independent [29,31,32]. In human cGvHD, alloreactive B-cell responses are associated with elevated B-cell activating factor levels and activation of Bruton tyrosine kinase, spleen tyrosine kinase and B-cell linker [33].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological targeting of the JAK-STAT pathway was significantly efficacious in both the acute and chronic GvHD preclinical models tested. However, several pathological mechanisms utilize downstream signaling pathways that are potentially JAK-STAT-independent [29,31,32]. In human cGvHD, alloreactive B-cell responses are associated with elevated B-cell activating factor levels and activation of Bruton tyrosine kinase, spleen tyrosine kinase and B-cell linker [33].…”
Section: Discussionmentioning
confidence: 99%
“…[92,93]. As such, it does not seem unlikely that they contribute to the pathogenesis of CLAD, and further investigation is warranted [94][95][96].…”
Section: Mechanisms Of Damagementioning
confidence: 99%
“…Studies have shown that type 2 innate lymphoid cells (ILC2s) recruit myeloid-derived suppressor cells that suppress T cell-mediated GVHD and ILC3s secreting IL-22, enhancing intestinal stem cell function, promoting repair and the release of adenosine and suppressing T cell proliferation [ 61 , 62 , 63 , 64 , 65 ]. It is likely that an altered or reduced number of ILCs play some role under allogeneic circumstances of the ocular surface of dry eye associated with cGVHD.…”
Section: Ocular Surface Inflammationmentioning
confidence: 99%